EXTH-69. ASTROCYTOMA CELLS HARBORING MUTANT IDH1 ARE UNIQUELY SENSITIVE TO INHIBITION OF OXIDATIVE PHOSPHORYLATION. (14th November 2022) - Gurjar, Anagha; Colman, Howard; Holmen, Sheri
Abstract: BACKGROUND: Diffuse gliomas are the most common primary brain tumor in adults, affecting 20, 000 people in the United States each year. Current treatment modalities, which include surgery, radiation, and chemotherapy, are relatively ineffective against these tumors and the prognosis is poor. Although most cancer cells rely on glycolysis to generate ATP, IDH1 mutant gliomas show enhanced dependence on oxidative phosphorylation. Thus, we evaluated the effect of IACS-010759, a potent and selective inhibitor of complex I that interferes with cellular respiration, in multiple patient-derived glioma cells. METHODS: In the present study, we used six different patient-derived glioma cell cultures including four that are IDH1 wild type (wt) (GSC 20, GSC 23, LN 18 and SF 268) and two that are IDH1 R132H mutant (BT142 & 21238-IDH1 R132H ). All cells were cultured as neurospheres to maintain glioma stem cell (GSC) culture conditions. The toxicity of IACS-010759 was also evaluated in immortal non-transformed mouse astrocytes. Neurospheres and astrocytes were treated with IACS-010759 (0.1 µM-100 µM) and cell viability was evaluated after 72 hours using CellTiter-Glo. RESULTS: Inhibition of oxidative phosphorylation significantly reduced cell proliferation in all glioma cells evaluated. The IC50 of IACS-010759 ranged from 0.7 nM-100 µM but was lowest in IDH1 R132H astrocytoma cells, supporting the hypothesis that IDH1 mutant astrocytoma cells have enhanced dependence on oxidative phosphorylation. Importantly, immortal, non-transformed astrocytes were relatively resistant to IACS-010759 suggesting that this strategy may have an effective therapeutic window in this disease. CONCLUSION: In summary, IACS-010759-induced inhibition of oxidative phosphorylation elicited pronounced anti-neoplastic responses in vitro, especially in astrocytomas expressing mutant IDH1. IACS-010759 may be a promising therapy for both IDH1 wt and mutant gliomas, and we are currently evaluating the efficacy of this strategy in glioma mouse models.